The Influence of the Addition of Ca, Zn, and Zr on the Corrosion Properties of As-Homogenized Mg-3Sn Alloys - Zheng Jia; Yongzhi Yu; Zhiwen Mao; Sichao Du; Qiuli Chen; Xiaowei Niu (Crystals)
The influences of the addition of Ca, Zn, and Zr on the corrosion behavior and mechanism of as-homogenized Mg-3Sn (T3) alloys in a 3.5% NaCl solution were systematically investigated via hydrogen evolution, mass loss, and electrochemical tests. The results indicated that the addition of Ca resulted in a decrease in the corrosion resistance of the T3 alloy. However, the subsequent addition of Zn and Zr could enhance the corrosion resistance of the Mg-3Sn-1Ca (TX31) alloy. The primary cause for the decline in the corrosion resistance of the TX31 alloy was that Ca altered the type of the second phase and the corrosion mechanism of the T3 alloy. This was attributed to the fact that the addition of Ca in the T3 alloy induced the precipitation of the CaMgSn phase and inhibited the precipitation of the Mg2Sn phase. Simultaneously, both the average grain size and the area fraction of the second phase increased, which provided more initiation sites for pitting and accelerated the corrosion of the alloy. The addition of Zr in the TX31 alloy could remarkably refine grains, inhibit anodic corrosion, and improve corrosion resistance. Nevertheless, the corrosion resistance of the Mg-3Sn-1Ca-1Zr (TXK311) alloy was still inferior to that of the T3 alloy. In this study, the Mg-3Sn-1Ca-1Zn (TXZ311) alloy exhibited the best corrosion resistance, with a hydrogen-evolution corrosion rate of 2.82 mm·year−1. This was because the addition of Zn refined the grains of the TX31 alloy and facilitated the formation of a relatively stable passivation film, which effectively prevented the intrusion of Cl−, thereby enhancing the corrosion resistance of the alloy.